Analysis of Transient Stability in Multimachine systems considering AVR control in DIgSILENT's PowerFactory software (Ciencias de la Ingeniería y Aplicadas, 2023)
In this work a transient stability analysis will be performed, since, in the field of Electrical Engineering these studies are of great importance in the phase of preoperativity of the electrical power system, which implies that angular stability studies of the electrical system must be performed, using specialized software such as DiGSILENT PowerFactorand would facilitate this analysis, in order to verify the correct behaviour of synchronous machines connected to the electrical power system and to make an analysis of the variables affected, the main ones are : rotor angle, voltage in generating terminals, excitation voltage and active power delivered by the synchronous generator in the event of a contingency, which can be: short circuit events, disconnection of large load blocks, outputs of generating units. In this work, the stability study was performed in DiGSILENT PowerFactory with proposed case studies for the simulation of electromechanical transients, and considering the implementation of the AVR control (Automatic Voltage Control).
Keywords: Contingency; Stability; Synchronous generator; Electromagnetic transient